Water-oxygen barrier film based on polymer nanocomposite and preparation method of water-oxygen barrier film

By introducing CTAC-modified Laponite-PMMA composite materials into the inorganic/organic stacked films of flexible display devices, an inorganic/organic/inorganic overlapping structure film was prepared, which solved the problem of insufficient water and oxygen barrier performance of flexible display devices and achieved efficient water and oxygen barrier and mechanical stability.

CN120711940APending Publication Date: 2025-09-26XIAN TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510923381.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The inorganic/organic laminated films of existing flexible display devices have deficiencies in water and oxygen barrier properties and flexibility, and cannot meet the packaging requirements of water and oxygen sensitive flexible display devices.

Method used

A method for preparing a water and oxygen barrier film using polymer nanocomposites is adopted. By adding modified nanocomposites into high molecular polymers, an inorganic/organic/inorganic overlapping structure film is prepared, and CTAC is used to modify the Laponite-PMMA composite film layer to enhance the water and oxygen barrier performance.

Benefits of technology

It significantly improves the bending mechanical stability and water-oxygen barrier properties of the film layer, extends the length of the water-oxygen molecule transmission path, and meets the packaging requirements of water-oxygen sensitive flexible display devices such as OLED.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120711940A_ABST
    Figure CN120711940A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a water-oxygen barrier film based on a polymer nano composite material. The preparation method comprises the following steps: step 1, organically modifying Laponite; 2, a CTAC modified Laponite-PMMA precursor solution is prepared, and the CTAC modified Laponite-PMMA precursor solution is prepared; step 3, cleaning the flexible substrate and activating the surface of the flexible substrate; 4, depositing a first layer of inorganic thin film on the flexible substrate subjected to cleaning and surface activation in the step 3, and performing surface activation on the first layer of inorganic thin film; step 5, preparing a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in the step 4 by adopting the CTAC modified Laponite-PMMA precursor solution prepared in the step 2; and step 6, depositing a second layer of inorganic film on the modified CTAC-Laponite-PMMA composite film layer to obtain the inorganic / organic / inorganic overlapped structure water oxygen barrier film. The invention also discloses the water-oxygen barrier film prepared by the method, the bending mechanical stability of the water-oxygen barrier film is obviously improved, and research finds that the film still has good water vapor barrier performance after being repeatedly bent for 6000 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor thin film packaging, and relates to a water-oxygen barrier film based on polymer nanocomposites. The present invention also relates to a method for preparing the water-oxygen barrier film. Background Art

[0002] With the rapid development of next-generation information technologies such as artificial intelligence, the Internet of Things, and smart wearables, displays, as core carriers of information visualization and interactive interfaces, are facing complex technical demands for thinness, flexibility, low power consumption, large size, and low cost. This is driving the evolution of display technology towards flexibility, transcending the constraints of physical form. For flexible display technology, traditional glass cover packaging is difficult to apply to flexible display devices due to the fragility of glass. Therefore, developing flexible packaging technologies with ultra-low water vapor transmission rate (WVTR) and oxygen transmission rate (OTR) is critical to ensuring the display quality and service life of flexible displays.

[0003] With the continuous development of thin film preparation technology, thin film encapsulation technology has emerged. Depending on the film material, thin film encapsulation technology can be divided into three categories: inorganic thin film encapsulation, organic thin film encapsulation, and inorganic / organic stacked thin film encapsulation. Inorganic encapsulation films made of materials such as silicon nitride, aluminum oxide, and silicon oxide have excellent water and oxygen barrier properties. However, inorganic encapsulation films have poor flexibility and high brittleness. Repeated bending under mechanical stress can easily cause cracks, forming new water vapor permeation channels and accelerating water and oxygen permeation. Therefore, the application of single inorganic encapsulation films in flexible packaging has certain limitations. In contrast, organic encapsulation films such as polymethyl methacrylate (PMMA), fluororesin, and epoxy resin have excellent flexibility and high tensile strength, but their water and oxygen barrier properties are poor and cannot meet the encapsulation requirements of flexible display devices. Inorganic / organic laminated films combine the excellent barrier properties of inorganic films with the superior flexibility of organic films. They not only reduce stress mismatch between films, enhance the overall flexibility of the encapsulation film, and mitigate mechanical damage caused by bending, but also extend the permeation path for water and oxygen molecules through a "defect decoupling effect," reducing the impact of defects in the inorganic layer and effectively improving the water and oxygen barrier properties of the encapsulation film. Therefore, inorganic / organic laminated films are considered one of the most promising flexible encapsulation technologies.

[0004] Although inorganic / organic laminated films have both high barrier properties and excellent flexibility, the extremely high requirements for water and oxygen barrier performance for water and oxygen sensitive flexible display devices such as organic light-emitting diodes (OLEDs) and problems such as internal defects, residual stress, and interface mismatch in inorganic / organic films still affect the film encapsulation barrier performance to a certain extent. Therefore, the water and oxygen barrier capability of laminated films needs to be further improved. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing a water-oxygen barrier film based on polymer nanocomposites. By adding modified nanocomposites to high molecular polymers, the transmission path length and difficulty of water and oxygen molecules are effectively extended, thereby optimizing the water-oxygen barrier performance.

[0006] Another object of the present invention is to provide a water and oxygen barrier film prepared by the above-mentioned preparation method, which has good bending mechanical stability and water vapor barrier performance, and can meet the stringent requirements of water and oxygen barrier performance for water and oxygen sensitive flexible display devices such as OLED.

[0007] The technical solution adopted by the present invention is a method for preparing a water and oxygen barrier film based on a polymer nanocomposite material. The specific preparation steps are as follows: Step 1: organically modifying Laponite; Step 2: preparing a hexadecyltrimethylammonium chloride (CTAC)-modified laponite-polymethyl methacrylate (Laponite-PMMA) precursor solution; Step 3: Cleaning and surface activation of the flexible substrate; Step 4: depositing a first inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first inorganic thin film; Step 5: Using the CTAC-modified Laponite-PMMA precursor solution prepared in step 2, a modified CTAC-Laponite-PMMA composite film layer is prepared on the first inorganic film activated in step 4; Step 6: depositing a second inorganic thin film on the modified CTAC-Laponite-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film.

[0008] The present invention is also characterized in that: The specific steps of organic modification of Laponite in step 1 are as follows: Step 1.1, dissolve Laponite powder weighed to 0.03-0.2 mol / L in deionized water, and stir at room temperature for 1 h-3 h to prepare a Laponite deionized water dispersion; Step 1.2, dissolve CTAC in deionized water at a weight of 0.05 mol / L-0.2 mol / L, and heat with stirring at 40°C-80°C for 1 h-3 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 12 h to 48 h to achieve organic modification of Laponite, and obtaining a mixture of Laponite and CTAC; Step 1.4: Centrifuge the Laponite and CTAC mixture at 4000-12000 rpm for 10-40 min, filter the centrifuge to obtain a precipitate, and dry the precipitate in a drying oven at 70°C-120°C for 12-36 h to obtain CTAC-modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

[0009] The specific preparation steps of the CTAC-modified Laponite-PMMA precursor solution in step 2 are as follows: Step 2.1, CTAC-Laponite powder was weighed at a concentration of 0.05 mol / L to 0.2 mol / L and dissolved in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution; Step 2.2, PMMA powder was weighed at 0.05 mol / L to 0.2 mol / L and dissolved in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 3 wt% to 12 wt%, and stir at room temperature for 12 h to 36 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0010] The specific steps for cleaning and surface activation of the flexible substrate in step 3 are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 60°C-120°C for 1h-5h; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use any one of N2, Ar, and O2 as the cleaning gas. At a plasma processing power of 30W-100W and a gas flow rate of 10sccm-100sccm, perform plasma treatment for 5min-20min and set aside.

[0011] The specific steps of step 4 are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 80°C to 200°C, a first inorganic thin film of 50nm to 200nm is deposited on the flexible substrate by PECVD; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, any one of N2, Ar, and O2 gases is used as a cleaning gas, and plasma treatment is performed for 5min-20min at a plasma treatment power of 30W-100W and a gas flow rate of 10sccm-100sccm to activate the surface of the first layer of inorganic thin film.

[0012] The specific process of forming the modified CTAC-Laponite-PMMA composite film layer in step 5 is as follows: the CTAC-modified Laponite-PMMA precursor liquid is ultrasonically mixed, and then dropped onto the first inorganic film layer after surface activation to form a 50nm-200nm modified Laponite-PMMA wet film on the first inorganic film layer; then the modified Laponite-PMMA wet film is placed on a hot plate and annealed at 50°C-100°C for 0.5h-2h to obtain a modified CTAC-Laponite-PMMA composite film layer.

[0013] The process of depositing a second layer of inorganic film on the modified CTAC-Laponite-PMMA composite film layer in step 6 is as follows: at a temperature of 80°C-200°C, PECVD is used to deposit a second layer of inorganic film of 50nm-200nm on the modified CTAC-Laponite-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film.

[0014] The flexible substrate is a polyimide flexible substrate.

[0015] The first inorganic thin film in step 5 and the second inorganic thin film in step 7 are any one of SiNx thin films, SiO2 thin films or SiON thin films.

[0016] The second technical solution adopted by the present invention is that the water and oxygen barrier film based on polymer nanocomposite materials is prepared by the above-mentioned preparation method, and its structure from the inside to the outside is a first inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second inorganic film layer; the first inorganic film layer and the second inorganic film layer are any one of SiNx film, SiO2 film or SiON film; the thickness of the first inorganic film layer and the second inorganic film layer is 50nm-200nm, and the thickness of the modified CTAC-Laponite-PMMA composite film layer is 50nm-200nm.

[0017] In the present application, PMMA is polymethyl methacrylate; Laponite is hectorite; CTAC is hexadecyltrimethylammonium chloride; PECVD is a special equipment for plasma enhanced chemical vapor deposition technology; and DMAC is N,N-dimethylacetamide.

[0018] The beneficial effects of the present invention are: 1) The present invention's method for preparing a water-oxygen barrier film based on a polymer nanocomposite material, compared to existing technologies, utilizes organic glass (PMMA) as the primary organic material in the water-oxygen barrier film. This utilizes PMMA's superior optical properties to replace the high optical transmittance of traditional rigid glass packaging. Furthermore, PMMA's ease of processing and process compatibility reduce the difficulty of industrialization. To address PMMA's poor water-oxygen barrier performance, Laponite is used as an inorganic nanosheet reinforcement for the PMMA polymer. Bulk-modification of PMMA effectively extends the transport path length and difficulty of water and oxygen molecules within the composite film compared to traditional PMMA films, thereby improving the film's water-oxygen barrier performance. To address Laponite's poor dispersibility in PMMA, CTAC is used to organically modify Laponite. This allows long quaternary ammonium salt chains to penetrate the Laponite interlayers, coating the Laponite sheet surface with long alkyl carbon chains. This enhances the sheet's hydrophobicity, effectively improving the compatibility of the Laponite nanosheets in PMMA and ultimately significantly enhancing the dispersibility of the Laponite nanosheets in PMMA. In order to solve the problem of serious deterioration of surface roughness of highly doped Laponite inorganic nanosheet PMMA composite film layer, CTAC-modified Laponite is used as the inorganic nanosheet layer reinforcement of polymer PMMA, which significantly reduces the surface roughness of the composite film layer, so that the modified Laponite inorganic nanosheet PMMA composite film layer can be better applied to multilayer film structure, thereby more effectively improving the water and oxygen barrier performance of the overlapping structure water and oxygen barrier film layer.

[0019] 2) The water-oxygen barrier film based on polymer nanocomposites of the present invention significantly improves the bending mechanical stability of the film layer. Studies have found that after repeated bending 6,000 times, the film layer still has good water vapor barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the structure of the SiNx / CTAC-Laponite-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in Example 1; Figure 2 1 is a static water contact angle measurement diagram of the modified CTAC-Laponite-PMMA composite film prepared in Example 1; Figure 3 is an AFM spectrum of the CTAC-Laponite (8 wt %)-PMMA composite film prepared in Example 1; Figure 4 is the curve of normalized conductivity changing with time and WVTR value; Figure 5 It is the discounted graph of WVTR changing with the number of bends; Figure 6 Schematic diagram of the structure of the SiNx / Laponite-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in Comparative Example 1 and Comparative Example 2; Figure 7 This is a static water contact angle measurement diagram of the Laponite (8 wt%)-PMMA composite film prepared in Comparative Example 1; Figure 8 This is the AFM spectrum of the Laponite (8 wt%)-PMMA composite film prepared in Comparative Example 1; Figure 9 This is the AFM spectrum of the Laponite (5 wt%)-PMMA composite film prepared in Comparative Example 2; Figure 10 Schematic diagram of the structure of the SiNx / PMMA / SiNx overlapping structure water and oxygen barrier film prepared in Comparative Example 3; Figure 11 This is the AFM spectrum of the PMMA film in Comparative Example 3. DETAILED DESCRIPTION

[0021] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0022] The flexible substrates in the embodiments of the present application are all PI substrates, ie, polyimide substrates.

[0023] Example 1 In this example, a SiNx / CTAC-Laponite (8 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film based on a polymer nanocomposite material was prepared. The specific preparation steps are as follows: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1, dissolve Laponite powder weighed to 0.07 mol / L in deionized water and stir at room temperature for 2 h to obtain a Laponite deionized water dispersion; Step 1.2: Dissolve CTAC in deionized water at a weight of 0.1 mol / L and heat with stirring at 50°C for 2 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 24 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 8000 rpm for 20 min, filter the centrifuge to obtain a precipitate, and dry the precipitate at 90°C for 24 h to obtain CTAC-modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

[0024] Step 2: The specific steps for preparing the CTAC-modified Laponite-PMMA precursor solution are as follows: Step 2.1: Weigh 0.1 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weighing PMMA powder at 0.1 mol / L and dissolving it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add 8 wt % of the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution and stir at room temperature for 24 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0025] Step 3: The specific steps for cleaning and surface activation of the flexible substrate are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 80°C for 2 hours; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use Ar as the cleaning gas, and perform plasma treatment for 10 minutes at a plasma treatment power of 50 W and a gas flow rate of 50 sccm.

[0026] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 100° C., a 100 nm thick SiNx thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, Ar is used as the cleaning gas, and plasma treatment is performed for 10 minutes at a plasma treatment power of 50 W and a gas flow rate of 50 sccm to activate the surface of the first layer of inorganic thin film.

[0027] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation, and use spin coating to form a 100 nm modified Laponite-PMMA wet film on the first inorganic thin film; then place the modified Laponite-PMMA wet film on a hot plate and anneal at 90°C for 1 hour to obtain a modified CTAC-Laponite (8wt%)-PMMA composite film layer.

[0028] Step 6. Deposit a second inorganic film on the modified CTAC-Laponite (8wt%)-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 100°C, use PECVD to deposit a 100nm SiNx film as the second inorganic film on the modified CTAC-Laponite (8wt%)-PMMA composite film layer to obtain a SiNx / CTAC-Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film.

[0029] The SiNx / CTAC-Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this embodiment has a structure consisting of a first SiNx inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second SiNx inorganic film layer from the inside to the outside; the thickness of the first SiNx inorganic film layer and the second SiNx inorganic film layer are both 100 nm, and the thickness of the CTAC-Laponite (8wt%)-PMMA composite film layer is 100 nm.

[0030] The structure of the water and oxygen barrier film prepared in this embodiment is shown in FIG. Figure 1 shown.

[0031] The surface wettability and surface morphology of the CTAC-Laponite (8 wt%)-PMMA composite film prepared in this example were tested. The surface wettability was tested using a static water contact angle meter. The test results are shown in Figure 2. Figure 2 As shown, the surface morphology was tested by AFM, and the test results are as follows Figure 3 As shown; The performance and bending stability test of the SiNx / CTAC-Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this example: The water and oxygen barrier performance of the overlapping film layer under different bending times was tested using the Ca test method. The curve of the change of the normalized conductivity of the sample over time and the WVTR value are shown in Figure 2. Figure 4 As shown in the figure, the curve of WVTR changing with the number of bends is as follows: Figure 5 shown.

[0032] Comparative analysis of excellence: (1) Figure 2 It can be seen that the SiNx / CTAC-Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this embodiment is hydrophobic, which is beneficial to reduce the absorption of water vapor by the film layer; (2) Figure 3 It can be seen that the SiNx / CTAC-Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this embodiment has good surface quality; (3) Figure 4 and Figure 5 It can be seen that the SiNx / CTAC-Laponite (8 wt %)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this example exhibits good water vapor barrier properties and good mechanical stability.

[0033] Example 2 This example prepares a water and oxygen barrier film having a SiO2 / CTAC-Laponite (3 wt%)-PMMA / SiO2 overlapping structure based on a polymer nanocomposite material. The specific preparation steps are as follows: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1, dissolve Laponite powder weighed to 0.03 mol / L in deionized water and stir at room temperature for 3 h to obtain a Laponite deionized water dispersion; Step 1.2: Dissolve CTAC in deionized water at a weight of 0.05 mol / L and heat with stirring at 40°C for 3 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 12 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 4000 rpm for 40 min, filter the centrifuge to obtain a precipitate, and dry the precipitate at 70°C for 36 h to obtain CTAC-modified Laponite crystals. Grind and sieve to obtain CTAC-Laponite powder, which is then sealed and stored for later use.

[0034] Step 2: The specific steps for preparing the CTAC-modified Laponite-PMMA precursor solution are as follows: Step 2.1: Weigh 0.05 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weigh PMMA powder at 0.05 mol / L and dissolve it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 3 wt %, and stir at room temperature for 12 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0035] Step 3: The specific steps for cleaning and surface activation of the flexible substrate are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 60°C for 5 hours; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use Ar as the cleaning gas, and perform plasma treatment for 5 minutes at a plasma treatment power of 30 W and a gas flow rate of 10 sccm.

[0036] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 80° C., a 50 nm thick SiO 2 thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, Ar is used as the cleaning gas, and plasma treatment is performed for 5 minutes at a plasma treatment power of 30 W and a gas flow rate of 10 sccm to activate the surface of the first layer of inorganic thin film.

[0037] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation, and use spin coating to form a 50nm modified Laponite-PMMA wet film on the first inorganic thin film; then place the modified Laponite-PMMA wet film on a hot plate and anneal at 50°C for 2h to obtain a modified CTAC-Laponite (3wt%)-PMMA composite film layer.

[0038] Step 6: Deposit a second inorganic thin film on the modified PMMA wet film to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 80°C, use PECVD to deposit a 50nm second inorganic thin film on the modified CTAC-Laponite (3wt%)-PMMA composite film layer to obtain a SiO2 / CTAC-Laponite (3wt%)-PMMA / SiO2 overlapping structure water and oxygen barrier film.

[0039] The SiO2 / CTAC-Laponite (3wt%)-PMMA / SiO2 overlapping structure water and oxygen barrier film prepared in this embodiment has a structure consisting of a first layer of SiO2 inorganic film, a modified CTAC-Laponite-PMMA composite film layer, and a second layer of SiO2 inorganic film from the inside to the outside; the thickness of the first layer of SiO2 inorganic film and the second layer of SiO2 inorganic film are both 50nm, and the thickness of the PMMA composite film layer is 50nm.

[0040] Example 3 The specific preparation steps of the SiON / CTAC-Laponite (12 wt%)-PMMA / SiON overlapping structure water and oxygen barrier film based on the polymer nanocomposite prepared in this embodiment are as follows: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1, dissolve Laponite powder weighed to 0.2 mol / L in deionized water and stir at room temperature for 1 h to obtain a Laponite deionized water dispersion; Step 1.2: Dissolve CTAC in deionized water at a weight of 0.2 mol / L and heat with stirring at 80°C for 1 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 48 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 12,000 rpm for 10 minutes, filter the centrifuge to obtain a precipitate, and dry the precipitate at 120°C for 12 hours to obtain modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

[0041] Step 2: Prepare modified Laponite-PMMA precursor solution. The specific preparation steps are as follows: Step 2.1: Weigh 0.2 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weighing PMMA powder at 0.2 mol / L and dissolving it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 12 wt %, and stir at room temperature for 36 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0042] Step 3: The specific steps for cleaning and surface activation of the flexible substrate are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and dry it in a drying oven at 120°C for 1 hour; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use O2 as the cleaning gas, and perform plasma treatment for 20 minutes at a plasma treatment power of 100 W and a gas flow rate of 100 sccm.

[0043] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 200° C., a 200 nm thick SiON thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, O2 is used as the cleaning gas, and plasma treatment is performed for 20 minutes at a plasma treatment power of 100 W and a gas flow rate of 100 sccm to activate the surface of the first layer of inorganic thin film.

[0044] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation, and use spin coating to form a 200nm modified Laponite-PMMA wet film on the first inorganic thin film; then place the modified Laponite-PMMA wet film on a hot plate and anneal it at 100°C for 0.5h to obtain a modified CTAC-Laponite (12wt%)-PMMA composite film layer.

[0045] Step 6: Deposit a second inorganic film on the modified PMMA wet film to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 200°C, use PECVD to deposit a 200nm SiON film as the second inorganic film on the modified CTAC-Laponite (12wt%)-PMMA composite film layer to obtain a SiON / CTAC-Laponite (12wt%)-PMMA / SiON overlapping structure water and oxygen barrier film.

[0046] The SiON / CTAC-Laponite (12 wt%)-PMMA / SiON overlapping structure water and oxygen barrier film prepared in this embodiment has a structure consisting of a first SiON inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second SiON inorganic film layer from the inside to the outside; the thickness of the first SiON inorganic film layer and the second SiON inorganic film layer are both 200 nm, and the thickness of the PMMA composite film layer is 200 nm.

[0047] Example 4 The SiON / CTAC-Laponite (10 wt%)-PMMA / SiON overlapping structure water and oxygen barrier film based on the polymer nanocomposite material prepared in this embodiment is prepared in the following specific steps: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1, dissolve Laponite powder weighed to 0.15 mol / L in deionized water and stir at room temperature for 1 h to obtain a Laponite deionized water dispersion; Step 1.2: Dissolve CTAC in deionized water at a weight of 0.1 mol / L and heat with stirring at 60°C for 2 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 40 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 10,000 rpm for 15 minutes, filter the centrifuge to obtain a precipitate, and dry the precipitate at 100°C for 20 hours to obtain CTAC-modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

[0048] Step 2: The specific steps for preparing the CTAC-modified Laponite-PMMA precursor solution are as follows: Step 2.1: Weigh 0.1 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weighing PMMA powder at 0.1 mol / L and dissolving it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 10 wt %, and stir at room temperature for 32 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0049] Step 3: Clean and activate the flexible substrate. The specific steps are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 100°C for 3 hours; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use N2 as the cleaning gas, and perform plasma treatment for 15 minutes at a plasma treatment power of 80 W and a gas flow rate of 80 sccm.

[0050] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 120° C., a 150 nm thick SiON thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, O2 is used as the cleaning gas, and plasma treatment is performed for 15 minutes at a plasma processing power of 80 W and a gas flow rate of 80 sccm to activate the surface of the first layer of inorganic thin film.

[0051] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation, and use spin coating to form a 150nm modified Laponite-PMMA wet film on the first inorganic thin film; then place the modified Laponite-PMMA wet film on a hot plate and anneal at 60°C for 1.5h to obtain a modified CTAC-Laponite (10wt%)-PMMA composite film layer.

[0052] Step 6: Deposit a second inorganic film on the modified PMMA wet film to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 150°C, PECVD is used to deposit a 150nm SiON film as the second inorganic film on the modified CTAC-Laponite (10wt%)-PMMA composite film layer to obtain a SiON / CTAC-Laponite (10wt%)-PMMA / SiON overlapping structure water and oxygen barrier film.

[0053] The SiON / CTAC-Laponite (10wt%)-PMMA / SiON overlapping structure water and oxygen barrier film prepared in this embodiment has a structure consisting of a first SiON inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second SiON inorganic film layer from the inside to the outside; the thickness of the first SiON inorganic film layer and the second SiON inorganic film layer are both 150nm, and the thickness of the PMMA composite film layer is 150nm.

[0054] Example 5 The SiO2 / CTAC-Laponite (5 wt%)-PMMA / SiON overlapping structure water and oxygen barrier film prepared in this embodiment is based on a polymer nanocomposite material. The specific preparation steps are as follows: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1, dissolve Laponite powder weighed to 0.06 mol / L in deionized water and stir at room temperature for 1 h to obtain a Laponite deionized water dispersion; Step 1.2: Weigh CTAC to 0.15 mol / L and dissolve it in deionized water. Heat and stir at 50°C for 2.5 h to obtain a CTAC aqueous solution. Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 36 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 9000 rpm for 12 minutes, filter the centrifuge to obtain a precipitate, and dry the precipitate at 80°C for 20 hours to obtain CTAC-modified Laponite crystals. Grind and sieve to obtain CTAC-Laponite powder, which is then sealed and stored for later use.

[0055] Step 2: The specific steps for preparing the CTAC-modified Laponite-PMMA precursor solution are as follows: Step 2.1: Weigh 0.08 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weigh PMMA powder at 0.08 mol / L and dissolve it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 5 wt %, and stir at room temperature for 20 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0056] Step 3: Clean and activate the flexible substrate. The specific steps are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 80°C for 4 hours; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use O2 as the cleaning gas, and perform plasma treatment for 20 minutes at a plasma treatment power of 80 W and a gas flow rate of 80 sccm.

[0057] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 200° C., a 100 nm thick SiO 2 thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, O2 is used as the cleaning gas, and plasma treatment is performed for 20 minutes at a plasma treatment power of 100 W and a gas flow rate of 100 sccm to activate the surface of the first layer of inorganic thin film.

[0058] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation, and use spin coating to form a 150nm modified Laponite-PMMA wet film on the first inorganic thin film; then place the modified Laponite-PMMA wet film on a hot plate and anneal at 100°C for 1h to obtain a modified CTAC-Laponite (5wt%)-PMMA composite film layer.

[0059] Step 6: Deposit a second inorganic film on the modified PMMA wet film to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 200°C, use PECVD to deposit a 150nm SiON film as the second inorganic film on the modified CTAC-Laponite (5wt%)-PMMA composite film layer to obtain a SiO2 / CTAC-Laponite (5wt%)-PMMA / SiON overlapping structure water and oxygen barrier film.

[0060] The SiO2 / CTAC-Laponite (5wt%)-PMMA / SiON overlapping structure water and oxygen barrier film prepared in this embodiment has a structure consisting of a first layer of SiO2 inorganic film, a modified CTAC-Laponite-PMMA composite film layer, and a second layer of SiON inorganic film from the inside to the outside; the thickness of the first layer of SiO2 inorganic film is 100nm, the thickness of the second layer of SiON inorganic film is 150nm, and the thickness of the PMMA composite film layer is 150nm.

[0061] Example 6 The SiON / CTAC-Laponite (12 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film based on the polymer nanocomposite material prepared in this embodiment is prepared in the following specific steps: Step 1: Organically modify Laponite. The specific steps are as follows: Step 1.1: Weigh 0.1 mol / L Laponite powder and dissolve it in deionized water. Stir at room temperature for 1 h to obtain a Laponite deionized water dispersion. Step 1.2: Dissolve CTAC in deionized water at a weight of 0.2 mol / L and heat with stirring at 80°C for 1 h to obtain a CTAC aqueous solution; Step 1.3, mixing equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 48 hours to achieve organic modification of Laponite and obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 12,000 rpm for 10 minutes, filter the centrifuge to obtain a precipitate, and dry the precipitate at 120°C for 12 hours to obtain modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

[0062] Step 2: The specific steps for preparing the CTAC-modified Laponite-PMMA precursor solution are as follows: Step 2.1: Weigh 0.2 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, weighing PMMA powder at 0.2 mol / L and dissolving it in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 12 wt %, and stir at room temperature for 36 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

[0063] Step 3: Clean and activate the flexible substrate. The specific steps are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and dry it in a drying oven at 120°C for 1 hour; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use O2 as the cleaning gas, and perform plasma treatment for 20 minutes at a plasma treatment power of 100 W and a gas flow rate of 100 sccm.

[0064] Step 4: depositing a first layer of inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first layer of inorganic thin film. The specific steps are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 200° C., a 100 nm thick SiON thin film is deposited on the flexible substrate by PECVD as the first inorganic thin film; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, O2 is used as the cleaning gas, and plasma treatment is performed for 20 minutes at a plasma treatment power of 100 W and a gas flow rate of 100 sccm to activate the surface of the first layer of inorganic thin film.

[0065] Step 5. Use the CTAC-modified Laponite-PMMA precursor prepared in step 2 to prepare a modified CTAC-Laponite-PMMA composite film layer on the inorganic thin film layer activated in step 4. The specific process is as follows: ultrasonically mix the CTAC-modified Laponite-PMMA precursor, and then drop it on the first inorganic thin film after surface activation. Use spin coating to form a 100 nm modified Laponite-PMMA wet film on the first inorganic thin film. Then, place the modified Laponite-PMMA wet film on a hot plate and anneal it at 100°C for 1 hour to obtain a modified CTAC-Laponite (12 wt%)-PMMA composite film layer.

[0066] Step 6: Deposit a second inorganic film on the modified PMMA wet film to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific process is as follows: At a temperature of 200°C, use PECVD to deposit a 150nm SiNx film as the second inorganic film on the modified CTAC-Laponite (12wt%)-PMMA composite film layer to obtain a SiON / CTAC-Laponite (12wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film.

[0067] The SiON / CTAC-Laponite (12 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this embodiment has a structure comprising, from the inside to the outside, a first SiON inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second SiNx inorganic film layer; the thickness of the first SiON inorganic film layer is 100 nm, the thickness of the second SiNx inorganic film layer is 150 nm, and the thickness of the PMMA composite film layer is 100 nm.

[0068] The performance advantages of the water and oxygen barrier film prepared by the present invention are further illustrated below through three comparative examples: Comparative Example 1 In this comparative example, a water and oxygen barrier film having an overlapping structure of an inorganic film layer / Laponite-PMMA composite film layer / inorganic film layer prepared based on bulk phase reinforcement was prepared. The specific preparation steps are as follows: Step 1: Preparation of Laponite dispersion based on N,N-dimethylacetamide (DMAC) solvent, specifically comprising the following steps: Step 1.1, dissolve Laponite powder weighed to 0.07 mol / L in deionized water and stir at room temperature for 2 h to obtain a Laponite deionized water dispersion; Step 1.2: Mix equal volumes of Laponite deionized water dispersion and DMAC solution and stir at room temperature for 4 h to obtain a clear and transparent DMAC mixture; Step 1.3: Evaporate the DMAC mixture on a rotary evaporator at 55° C. to remove water, thereby obtaining a transparent Laponite-free DMAC dispersion.

[0069] Step 2: Preparation of Laponite-PMMA precursor solution, specifically comprising the following steps: Step 2.1: Dissolve 0.1 mol / L PMMA powder in 50 mg / ml DMAC and stir at 55°C for 2 hours to obtain a clear PMMA solution. Step 2.2: Add 8 wt % of Laponite DMAC dispersion to the PMMA solution and stir at room temperature for 24 hours to obtain a modified Laponite (8 wt %)-PMMA precursor solution.

[0070] Step 3: Cleaning and surface activation of the flexible substrate. The specific steps are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 80°C for 2 hours; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use N2 as the cleaning gas, and perform plasma treatment for 10 minutes at a plasma treatment power of 50 W and a gas flow rate of 50 sccm.

[0071] Step 4: depositing a first inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and surface-activating the first inorganic thin film. SiNx is selected as the first inorganic thin film. The specific steps are the same as step 4 in embodiment 1.

[0072] Step 5. Preparation of Laponite (8%)-PMMA composite film layer: The Laponite-PMMA precursor solution prepared in step 2 was ultrasonically mixed and then dropped onto the first SiNx film layer after surface activation. A 100 nm Laponite-PMMA wet film was formed on the SiNx film layer by spin coating. The Laponite-PMMA wet film was then placed on a hot plate and annealed at 90°C for 1 h to remove residual solvent, thereby obtaining a Laponite (8 wt%)-PMMA composite film layer.

[0073] Step 6: Deposit a second inorganic thin film on the Laponite (8wt%)-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The specific steps are the same as Step 6 in Example 1 to obtain a SiNx / Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film.

[0074] The film structure of the SiNx / Laponite (8 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example is as follows: Figure 6 shown.

[0075] The surface wettability and surface morphology of the Laponite (8wt%)-PMMA composite film prepared in this comparative example were tested. The surface wettability was tested using a static water contact angle meter. The test results are shown in Figure 2. Figure 7 As shown, the surface morphology was tested by AFM, and the test results are as follows Figure 8 As shown; the membrane structure diagram is as follows Figure 8 shown.

[0076] The barrier performance and bending stability test of the SiNx / Laponite (8wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example: The water and oxygen barrier performance of the overlapping film layer under different bending times was tested using the Ca test method. The curve of the change of the normalized conductivity of the sample with time and the WVTR value are shown in Figure 2. Figure 4 As shown in the figure, the curve of WVTR changing with the number of bends is as follows: Figure 5 shown.

[0077] Comparative analysis of excellence: (1) Figure 2 and Figure 7 It can be seen that the SiNx / Laponite (8 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example exhibits hydrophobicity, but its hydrophobicity is significantly reduced compared with the SiNx / CTAC-Laponite (8 wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in Example 1. Therefore, the water vapor barrier ability of the composite film prepared in this comparative example is inferior to that of the composite film prepared in Example 1; (2) Comparison Figure 3 and Figure 8 It can be seen that the surface quality of the Laponite (8%)-PMMA composite film layer prepared in this comparative example is significantly worse than that of the CTAC-Laponite (8%)-PMMA composite film layer prepared in Example 1, which is not conducive to the deposition quality of the subsequent overlapping film layers; (3) Figure 4 and Figure 5 It can be seen that the SiNx / Laponite (8%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example exhibits good water vapor barrier properties and good mechanical stability, but both are inferior to Example 1.

[0078] Comparative Example 2 The water and oxygen barrier film based on the overlapping structure of bulk-reinforced inorganic film layer / Laponite inorganic nanosheet PMMA composite film layer / inorganic film layer prepared in this comparative example is specifically prepared in the following steps: Step 1: Preparation of Laponite dispersion based on N,N-dimethylacetamide (DMAC) solvent. The specific steps are the same as Step 1 in Comparative Example 1.

[0079] Step 2, preparing a Laponite-PMMA precursor solution, specifically comprising the following steps: weighing PMMA powder at a concentration of 0.1 mol / L, dissolving it in DMAC (50 mg / ml), and stirring at 55° C. for 2 hours to obtain a clear and transparent PMMA solution.

[0080] Step 3: Cleaning and surface activation of the flexible substrate. The specific steps are the same as Step 3 of Example 1.

[0081] Step 4: depositing a first inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and surface-activating the first inorganic thin film. The first inorganic thin film is made of SiNx with a film thickness of 100 nm. The specific steps are the same as step 4 in embodiment 1.

[0082] Step 5: Preparation of Laponite (5%)-PMMA composite film layer The Laponite-PMMA precursor prepared in step 2 was ultrasonically mixed and then dropped onto the first SiNx film layer after surface activation. A 100 nm Laponite-PMMA wet film was formed on the SiNx film layer by spin coating. The Laponite-PMMA wet film was then placed on a hot plate and annealed at 90°C for 1 h to remove the residual solvent, thereby obtaining a Laponite (5 wt%)-PMMA composite film layer.

[0083] Step 6. Deposit a second inorganic film layer on the Laponite (5wt%)-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The second inorganic film layer is SiNx, and the film thickness is 100 nm. The specific steps are the same as Step 6 in Example 1 to obtain a SiNx / Laponite (5wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film.

[0084] The structure of the SiNx / Laponite (5wt%)-PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example is as follows Figure 6 shown.

[0085] The surface morphology of the Laponite (5%)-PMMA composite film prepared in this comparative example was tested by AFM. The test results are as follows: Figure 9 shown.

[0086] The water and oxygen barrier film prepared in this comparative example is tested for its barrier properties: the curve of the change of the normalized conductivity of the sample over time and the WVTR value are shown in FIG. Figure 4 shown.

[0087] Comparative analysis of excellence: (1) Comparison Figure 3 、 Figure 8 and Figure 9 It can be seen that reducing the composite concentration of Laponite in PMMA can reduce the surface roughness of the Laponite-PMMA composite film layer, but its surface roughness is still much higher than that of the CTAC-Laponite (8wt%)-PMMA composite film layer prepared in Example 1, which is still not conducive to the deposition quality of the subsequent overlapping film layer, thereby affecting the water and oxygen barrier capacity of the overlapping structure water and oxygen barrier film; (2) Figure 4It can be seen that the water vapor barrier capability of the overlapping structure water and oxygen barrier film prepared in this comparative example is further reduced compared to Comparative Example 1 due to the reduced composite concentration of Laponite in PMMA. In summary, it can be seen that reducing the composite concentration of Laponite in PMMA can improve the surface roughness of the Laponite-PMMA composite film to a certain extent, but it also shortens the water and oxygen transmission path in the composite film, resulting in a deterioration in the water and oxygen barrier performance of the overlapping structure water and oxygen barrier film prepared in this comparative example.

[0088] Comparative Example 3 This comparative example provides a method for preparing a water and oxygen barrier film having an inorganic film layer / PMMA / inorganic film layer overlapping structure. The specific preparation steps are as follows: Step 1. Preparation of PMMA DMAC precursor solution: Weigh 0.1 mol / L PMMA powder and dissolve it in DMAC (50 mg / ml). Stir at 55°C for 2 hours until the solution becomes clear and transparent. Step 2: Cleaning and surface activation of the flexible substrate, the specific steps are the same as step 3 in Example 1; Step 3: depositing a first inorganic thin film on the flexible substrate cleaned and surface activated in step 2, and surface-activating the first inorganic thin film. The first inorganic thin film is made of SiNx and has a thickness of 100 nm. The specific steps are the same as step 4 in embodiment 1. Step 4, Preparation of PMMA Film: The DMAC precursor solution prepared in Step 1 for PMMA was added dropwise to the first SiNx film layer after surface activation, and a 100 nm PMMA wet film was formed on the SiNx film layer by spin coating. The PMMA wet film was then placed on a hot plate and annealed at 90°C for 1 h to remove residual solvent, thereby obtaining a PMMA film layer. Step 5: Deposit a second inorganic film on the PMMA film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film. The second inorganic film layer is SiNx, and the film thickness is 100 nm. The specific steps are the same as step 6 in Example 1 to obtain a SiNx / PMMA / SiNx overlapping structure water and oxygen barrier film.

[0089] The SiNx / PMMA / SiNx overlapping structure water and oxygen barrier film prepared in this comparative example has a film layer structure as shown in FIG. Figure 10 shown.

[0090] The surface morphology of the PMMA film prepared in this comparative example was tested using AFM. The test results are as follows: Figure 11 As shown in FIG. 1 , the water and oxygen barrier performance of the overlapping structure water and oxygen barrier film prepared in this comparative example, the change curve of the normalized conductivity of the sample over time and the WVTR value are shown in FIG. Figure 4 shown.

[0091] Comparative analysis with Example 1 and Comparative Examples 1-2: 1) Comparison Figure 8 、 Figure 9 、 Figure 11 It can be seen that with the increase of Laponite composite concentration, the surface quality of Laponite-PMMA composite film further deteriorates. When there is no Laponite composite, the surface roughness is the smallest; 2) Comparison Figure 3 and Figure 11 It can be seen that after the organic modification of Laponite, the surface morphology of the composite film prepared in Example 1 did not deteriorate significantly, effectively avoiding the degradation of the subsequent overlapping film deposition quality; 3) Figure 4 It can be seen that the water and oxygen barrier capacity of the overlapping structure water and oxygen barrier film prepared in this comparative example is the worst, which further confirms the advantage of Example 1.

Claims

1. A method for preparing a water and oxygen barrier film based on a polymer nanocomposite material, characterized in that: The specific preparation steps are as follows: Step 1, organically modifying Laponite; Step 2, preparing a CTAC-modified Laponite-PMMA precursor solution; Step 3: Cleaning and surface activation of the flexible substrate; Step 4: depositing a first inorganic thin film on the flexible substrate cleaned and surface activated in step 3, and performing surface activation on the first inorganic thin film; Step 5: Using the CTAC-modified Laponite-PMMA precursor solution prepared in step 2, a modified CTAC-Laponite-PMMA composite film layer is prepared on the inorganic thin film layer activated in step 4; Step 6: depositing a second inorganic thin film on the modified CTAC-Laponite-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film.

2. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 1, characterized in that: The specific steps of organically modifying Laponite in step 1 are as follows: Step 1.1, dissolve Laponite powder weighed to 0.03-0.2 mol / L in deionized water, and stir at room temperature for 1 h-3 h to prepare a Laponite deionized water dispersion; Step 1.2, dissolve CTAC in deionized water at a weight of 0.05 mol / L-0.2 mol / L, and heat with stirring at 40°C-80°C for 1 h-3 h to obtain a CTAC aqueous solution; Step 1.3, dissolving equal volumes of Laponite deionized water dispersion and CTAC aqueous solution, stirring at room temperature for 12 h to 48 h to obtain a Laponite and CTAC mixture; Step 1.4: Centrifuge the Laponite and CTAC mixture at 4000-12000 rpm for 10-40 min, filter the centrifuge to obtain a precipitate, and dry the precipitate in a drying oven at 70°C-120°C for 12-36 h to obtain CTAC-modified Laponite crystals. Grind and sieve the CTAC-Laponite powder, which is then sealed and stored for later use.

3. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 2, characterized in that: The specific preparation steps of the CTAC-modified Laponite-PMMA precursor solution in step 2 are as follows: Step 2.1: Weigh 0.05 mol / L to 0.2 mol / L CTAC-Laponite powder and dissolve it in chlorobenzene to prepare a CTAC-Laponite chlorobenzene solution. Step 2.2, PMMA powder was weighed at 0.05 mol / L to 0.2 mol / L and dissolved in chlorobenzene to prepare a PMMA chlorobenzene solution; Step 2.3: Add the CTAC-Laponite chlorobenzene solution to the PMMA chlorobenzene solution at a ratio of 3 wt% to 12 wt%, and stir at room temperature for 12 h to 36 h to obtain a CTAC-modified Laponite-PMMA precursor solution.

4. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 3, characterized in that: The specific steps of cleaning and surface activation of the flexible substrate in step 3 are as follows: Step 3.1, ultrasonically clean the flexible substrate in deionized water, acetone, isopropyl alcohol, and deionized water for 10 min each; Step 3.2, remove the flexible substrate from the deionized water and place it in a drying oven at 60°C-120°C for 1h-5h; Step 3.3: Place the dried flexible substrate in a plasma cleaning machine. Under vacuum conditions at room temperature, use any one of N2, Ar, and O2 as the cleaning gas. At a plasma processing power of 30W-100W and a gas flow rate of 10sccm-100sccm, perform plasma treatment for 5min-20min and set aside.

5. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 4, characterized in that: The specific steps of step 4 are as follows: Step 4.1, the deposition process of the first inorganic thin film is as follows: at a temperature of 80°C to 200°C, a first inorganic thin film of 50nm to 200nm is deposited on the flexible substrate by PECVD; Step 4.2, the surface activation process of the first layer of inorganic thin film is as follows: the flexible substrate on which the first layer of inorganic thin film is deposited is placed in an ion cleaning machine, and under vacuum conditions at room temperature, any one of N2, Ar, and O2 gases is used as a cleaning gas, and plasma treatment is performed for 5min-20min at a plasma treatment power of 30W-100W and a gas flow rate of 10sccm-100sccm to activate the surface of the first layer of inorganic thin film.

6. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 5, characterized in that: The specific process of forming the modified CTAC-Laponite-PMMA composite film layer in step 5 is as follows: ultrasonically mixing the CTAC-modified Laponite-PMMA precursor solution, and then dropping it onto the first inorganic film layer after surface activation to form a 50nm-200nm modified Laponite-PMMA wet film on the first inorganic film layer; then placing the modified Laponite-PMMA wet film on a hot plate and annealing it at 50°C-100°C for 0.5h-2h to obtain a modified CTAC-Laponite-PMMA composite film layer.

7. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 6, characterized in that: The process of depositing a second inorganic film on the modified CTAC-Laponite-PMMA composite film layer in step 6 is as follows: at a temperature of 80°C-200°C, PECVD is used to deposit a 50nm-200nm second inorganic film on the modified CTAC-Laponite-PMMA composite film layer to obtain an inorganic / organic / inorganic overlapping structure water and oxygen barrier film.

8. The method for preparing a water and oxygen barrier film based on polymer nanocomposites according to claim 7, wherein the flexible substrate is a polyimide flexible substrate.

9. The method for preparing a water and oxygen barrier film based on a polymer nanocomposite material according to claim 8, wherein the first inorganic film layer in step 5 and the second inorganic film layer in step 7 are any one of a SiNx film, a SiO2 film, and a SiON film.

10. The water and oxygen barrier film based on polymer nanocomposite materials prepared by the preparation method according to any one of claims 1 to 9, wherein the structure thereof comprises, from the inside to the outside, a first inorganic film layer, a modified CTAC-Laponite-PMMA composite film layer, and a second inorganic film layer; the first inorganic film layer and the second inorganic film layer are any one of SiNx film, SiO2 film or SiON film; the thickness of the first inorganic film layer and the second inorganic film layer are both 50nm-200nm, and the thickness of the modified CTAC-Laponite-PMMA composite film layer is 50nm-200nm.

Citation Information

Cited By

  • Preparation method of graphene-based water-oxygen barrier film and graphene-based water-oxygen barrier film

    CN121968986A